Penerapan Berat Barang Bukti Sebagai Syarat Pemberian Rehabilitasi Medis Terhadap Pecandu Narkotika Analisis Putusan Tinggi Mataram Nomor:89/PID.SUS/2020/PT.MTR - Marsel Mulyadi; Adhari, Ade (Jurnal Ilmu Hukum, Humaniora dan Politik, 2024)
The Indonesian state is a legal state, and is not based on mere power, and every legal state definitely has a constitution and laws (laws) that regulate the running system for everything in the country. The first starts from the relationship between citizens and the second to the relationship between citizens and the State. Regulations from one of the legal studies or fields of law in Indonesia and every individual has the right to legal protection and legal certainty as stated in the law (1945 Constitution of the Unitary State of the Republic of Indonesia Article 28D paragraph 1), and One of the laws in Indonesia is Criminal Law. In Indonesia, it is a law or regulation that regulates the conditions under which a person can be punished for an act he or she commits. Criminal law in Indonesia is regulated in the Criminal Code (KUHP). And specifically regarding legal certainty in providing medical rehabilitation to narcotics addicts. From the research results, several conclusions were obtained that according to the Supreme Court Circular Letter Number 4 of 2010, that a person is a narcotics addict whose weight of evidence is below the provisions stipulated in the Circular Letter Supreme Court (SEMA) Number 4 of 2010 is obliged to undergo medical rehabilitation and this is supplemented by Article 54 of Law Number 35 of 2009 concerning Narcotics. Based on this theory, a narcotics addict is obliged and entitled to undergo medical rehabilitation.